Self-heating and substrate effects in ultra-thin body ultra-thin BOX devices - S., Makovejev; V., Kilchytska; Mohd Khairuddin, Md Arshad; D., Flandre; F., Andrieu; O., Faynot; S., Olsen; J. P., Raskin (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/